Bioimaging: New Templated Ostwald Ripening Process of Mesostructured FeOOH for Third‐Harmonic Generation Bioimaging (Small 20/2019). Issue 20 (17th May 2019) - Lee, Chien‐Wei; Wu, Pei‐Chun; Hsu, I‐Ling; Liu, Tzu‐Ming; Chong, Wai‐How; Wu, Cheng‐Ham; Hsieh, Tsung‐Yuan; Guo, Lun‐Zhang; Tsao, Yu; Wu, Po‐Ting; Yu, Jiashing; Tsai, Pei‐Jane; et al.
Abstract : Third harmonic generation (THG) is a non‐bleaching contrast useful for long‐term cell tracking and in vivo angiography. However, high yields of THG in sub‐100 nm sized nanomaterials are challenging. In article number1805086, Tzu‐Ming Liu, Chih‐Chia Huang, and co‐workers successfully demonstrate in vitro and in vivo THG imaging with a mesostructured FeOOH synthesized through a new templated Ostwald ripening process.